1994
DOI: 10.1111/j.1365-2958.1994.tb00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth phase and low pH affect the thermal regulation of the Yersinia enterocolitica inv gene

Abstract: The inv gene encodes the protein invasin, which is the primary invasion factor for Yersinia enterocolitica in vitro and in vivo. Previous studies of Yersinia species have shown that inv expression and entry into mammalian cells are temperature regulated. Invasin production is reduced at the host temperature of 37 degrees C as compared to production at ambient temperature; consequently, this study was initiated to determine whether other host environmental signals might induce inv expression at 37 degrees C. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
160
2

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(172 citation statements)
references
References 49 publications
(38 reference statements)
10
160
2
Order By: Relevance
“…Cell invasion was shown to be solely mediated by the invasin protein, which was highly expressed at 37°C in all YeO:3 isolates, but not in YeO:8 strains (Uliczka et al, 2011). Latter observation is consistent with previous studies, demonstrating that inv expression in YeO:8 strain 8081v is mostly expressed at moderate temperature, whereas only very low amounts of invasin were detectable at 37°C (Pepe et al, 1994).…”
Section: Efficient Host Cell Adhesion and Invasion Of Yeo:3 Is Mediatsupporting
confidence: 81%
See 2 more Smart Citations
“…Cell invasion was shown to be solely mediated by the invasin protein, which was highly expressed at 37°C in all YeO:3 isolates, but not in YeO:8 strains (Uliczka et al, 2011). Latter observation is consistent with previous studies, demonstrating that inv expression in YeO:8 strain 8081v is mostly expressed at moderate temperature, whereas only very low amounts of invasin were detectable at 37°C (Pepe et al, 1994).…”
Section: Efficient Host Cell Adhesion and Invasion Of Yeo:3 Is Mediatsupporting
confidence: 81%
“…This strongly suggests that YadA and invasin of YeO:3 act cooperatively, whereby YadA promotes efficient cell attachment allowing invasin to initiate the entry process (figure 1). These properties seem to be YeO:3 specific, as previous studies with YeO:8 and Y. pseudotuberculosis showed that invasin and YadA are differentially expressed and constitute independent colonization factors that are active at separate sites and/or during different stages of the infection (Eitel & Dersch, 2002;Pepe et al, 1994;Skurnik & Toivanen, 1992).…”
Section: Efficient Host Cell Adhesion and Invasion Of Yeo:3 Is Mediatmentioning
confidence: 72%
See 1 more Smart Citation
“…Nonspecific antibodies were removed by adsorption of the sera with an acetone powders prepared from a cultures of Y. enterocolitica YEDS10 and E. coli containing pMAL-p2 (17). Polyclonal sera directed against chloramphenicol acetyl transferase and invasin were described (18,19). Polyclonal sera directed against ␤-lactamase was a gift (K. Postle, Washington State University).…”
Section: Methodsmentioning
confidence: 99%
“…It was therefore initially proposed that this adhesin contributed only to an acceleration of the early stages of host infection. However, two pieces of evidence suggested that regulation of inv transcription during infection may well depend on stimuli other than temperature (Pepe et al, 1994). Firstly, invasin can still be detected in murine Peyer's patches two days after oral challenge with Y. enterocolitica.…”
mentioning
confidence: 99%